The impact of the team games tournament cooperative learning model on students’ motivation and mathematics achievement in elementary schools - Setiana Setiana; Rahayu Condro Murti; Setiawan Edi Wibowo; Octavian Muning Sayekti (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This research investigates the positive influence of the Team Games Tournament (TGT) learning model on elementary school students' motivation and mathematics performance. Using a quantitative quasi-experimental design with a One Group Pre-test Post-test format, the study involved twenty-five students from class VB at Elementary School 006 Melayu Besar. Various data collection instruments were utilized, including observation sheets, motivation questionnaires, and evaluation tests for learning outcomes. Statistical analyses such as the Wilcoxon test, Paired Sample t-test, and MANOVA were conducted. Results revealed a significant Asymp.Sig (2-tailed) value below 0.001 in the Wilcoxon test, indicating that TGT significantly enhances learning motivation. The Paired Sample t-test also reported a p-value of <0.001, demonstrating a notable improvement in pre-test and post-test scores, affirming the effectiveness of the TGT model. Additionally, MANOVA analysis confirmed that the TGT model positively influences both motivation and mathematics learning outcomes simultaneously, highlighting its beneficial impact on elementary school students' academic achievements.